Pheno- and genotyping of Brucella abortus biovar 5 isolated from a water buffalo (Bubalus bubalis) fetus: First case reported in the Americas - Martínez, Diana; Thompson, Carolina Soledad; Draghi, Maria Graciela; Canavesio, Vilma; Jacobo, Roberto; Zimmer, Patricia Andrea; Elena, Sebastián Alejandro; Nicola, Ana M.; Torioni, Susana Marta (2018)
An isolate of Brucella spp. from an aborted water buffalo (Bubalus bubalis) fetus was characterized based on its pheno- and genotype. The phenotype was defined by carbon dioxide requirement, hydrogen sulfide production, sensitivity to thionin and basic fuchsin and agglutination with Brucella A and M monospecific antisera. The genotype was based on the amplification of the following genes: bcsp31, omp2ab, and eri and the species-specific localization of the insertion sequence IS711 in the Brucella chromosome via B. abortus–B. melitensis–B. ovis–B. suis (AMOS)-PCR. Unexpectedly, the isolate showed a phenotype different from B. abortus bv 1, the most prevalent strain in cattle in Argentina, and from vaccine strain 19, currently used in bovines and water buffaloes. Genotyping supported the phenotypic results, as the analysis of the omp2ab gene sequence showed an identical pattern to either B. abortus bv 5 or B. melitensis. Finally, the AMOS PCR generated a 1700-bp fragment from the isolate, different than those amplified from B. abortus bv 1 (498 bp) and B. melitensis (731 bp), confirming the presence of B. abortus bv 5. The OIE/FAO Reference Laboratory for Brucellosis confirmed this typing. This is the first report of B. abortus bv 5 from a water buffalo in the Americas.